STIMULASI PERKEMBANGAN MORAL ANAK USIA DINI MELALUI LIVING VALUES EDUCATION (LVE) DI RA TIARA CHANDRA YOGYAKARTA - Ria Astuti; Thorik Aziz (Liberi, 2023)
Indonesia has entered the demographic bonus, where the productive age is greater than the non-productive age. Therefore, the Government must prepare good early childhood education institutions to contribute to be of benefit to the Indonesian people. This is because early childhood is a golden phase. Ideally, a good PAUD institution is able to make a good curriculum. RA Tiara Chandra Yogyakarta created a values-based curriculum (LVE) to develop early childhood morale. In simple terms, this curriculummis a character-based curriculum. This type of research is descriptive qualitative, using interview, observationnand documentationntechniques. The resultssshowed thattthe curriculum used in RA Tiara Chandra is the 2013 Curriculum with the Living Values ​​Education (LVE) approach which contains universal values ​​in everyday life, both at school, home, and in the community. The method used is by modeling, habituation, role playing and telling stories.